EFFECT OF IONOSPHERIC INDUCED DEPOLARIZATION ON SATELLITE SOLAR POWER STATION - Chaudhary, K.; Vishvakarma, B. R. (Electromagnetics Academy, 2009)
—The paper presents the ionospheric effect on the power transmitted by satellite solar power station. Consequently, the Faraday rotation and losses due to ionospheric layer are calculated at 2.45 GHz frequency. It is observed that the fluctuation in the Faraday rotation in day time is found to be the maximum as compared to the night hours and. Loss due to depolarization is found to have the maximum value at noon hours for all the seasons (summer, winter and spring) however, the loss is the highest for summer season as compared to winter and spring season. This is logically correct because the ionization is the highest in summer in comparison to winter which gives rise to maximum electron content and maximum depolarization.